ANALISIS SENTIMEN APLIKASI MOBILE LEGENDS : BANG BANG MENGGUNAKAN LATENT DIRICHLET ALLOCATION - Muhammad Al Aziiz; Fariz Herlando; Muhammad Jeral Palepa; Reva Qintara Rohmansa (E-Link: Jurnal Teknik Elektro dan Informatika, 2024)
E-sports or electronic sports, is a video game competition in which players make video games as an alternative to officially recognized sports that have various values in the fields of sport, economics, social, achievement, and knowledge. Mobile Legends : Bang Bang is a mobile video game that goes into the multiplayer online battle arena genre (MOBA). These opinions need to be taken into account as input in the evaluation to ensure that the Mobile Legends: Bang Bang app can make a good impact on its users. In this study, data from the Google Play Store was used to analyze user responses to applications by classifying them into positive and negative categories. Furthermore, the Latent Dirichlet Allocation (LDA) method is used to group user opinions and identify topics that are frequently discussed. The results of the analysis showed that the majority of users responded positively to the Mobile Legends : Bang Bang application (72,7%) compared to negative (27,3%). The most frequently appearing words also indicate that positive sentiment words are more dominant than negative sentiment words.